Modelo Prolab: Cesta Maestra, una solución sostenible para fomentar el ahorro mediante la compra de productos próximos a vencer - Berrospi Marca, Nadia Katherine (2024)
Cesta Maestra project, which was developed applying the design thinking methodology, focuses on improving the savings capacity of its users, particularly those from the NSE C, by offering products that are soon to expire with discounts between 40% and 60%. This innovative solution not only encourages savings but also effectively addresses the reduction of food waste in supermarkets, still taking advantage of the high quality of these products that would otherwise be thrown away. In addition, Cesta Maestra establishes a beneficial relationship between supermarkets and suppliers, allowing them to reduce financial losses related to product expiration, improve inventory rotation, and reduce effort in terms of reverse logistics without the need to manage discounts directly at the points of service. Although facing challenges in technological implementation and coordination with supermarkets and suppliers, the project has demonstrated its viability through validations of usability, desirability, and feasibility. In financial terms, Cesta Maestra generates an economic NPV (EVAN) of US$1,309,090 with an IRR of 87.60%, reflecting its profitability and sustainability. On the other hand, the social impact is significant, generating a social NPV (VANS) of US$3,692,776, by directly mobilizing the Sustainable Development Goals (SDG) 2, 6, 12, 13, and 15, which include the reduction of hunger, the sustainable use of water resources, responsible consumption and production, climate action and the protection of terrestrial ecosystems. Finally, Cesta Maestra is presented as a comprehensive solution that not only offers economic benefits to consumers and commercial actors but also positively impacts the environment and society.